2022
DOI: 10.1111/btp.13121
|View full text |Cite
|
Sign up to set email alerts
|

Flammability in tropical savannas: Variation among growth forms and seasons in Cerrado

Abstract: Bradstock, 2010), which is the capacity of different plants and its components to burn and sustain a flame after encountering an ignition source (Anderson, 1970;Pausas, Keeley, & Schwilk, 2017). The most fire-prone ecosystems globally are tropical savannas (Bond & Van Wilgen, 1996;Simpson et al., 2016), covering about 20% of the Earth's land surface, due to the combination of highly seasonal rainfall and a continuous herbaceous layer that is typically dominated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Thermal analysis in the mid-infrared and thermal domains, including the mid-infrared (MIR: 2.5-8 µm) and thermal infrared (TIR: 8-14 µm) bands [86], allows us to determine the water stress plants are subjected to. This spatial behavior reflected in grassland covers, which have the highest level of variation for post-fire events in PBs, thus demonstrated that different forms of plant growth, such as grass, shrubs, and trees, presented varying levels of flammability, as well as revealing the dominant role that grasslands have as drivers of flammability in tropical savannas [87] by being the cover that is most affected by fire. Burned areas are also related to the continuity of fine combustible material and wind, where natural grassland flooded with a proliferation of Combretum spp.…”
Section: Discussionmentioning
confidence: 90%
“…Thermal analysis in the mid-infrared and thermal domains, including the mid-infrared (MIR: 2.5-8 µm) and thermal infrared (TIR: 8-14 µm) bands [86], allows us to determine the water stress plants are subjected to. This spatial behavior reflected in grassland covers, which have the highest level of variation for post-fire events in PBs, thus demonstrated that different forms of plant growth, such as grass, shrubs, and trees, presented varying levels of flammability, as well as revealing the dominant role that grasslands have as drivers of flammability in tropical savannas [87] by being the cover that is most affected by fire. Burned areas are also related to the continuity of fine combustible material and wind, where natural grassland flooded with a proliferation of Combretum spp.…”
Section: Discussionmentioning
confidence: 90%
“…The observed changes in abundance over time could influence ecological processes such as feedback between plants and fire, because graminoids are the major drivers of the flammability of Cerrado plant communities (Zanzarini et al, 2022). Moreover, the turnover of species observed among sites can also lead to a turnover of functional traits altering the ecosystem services, such as the type and presence of storage organs (Pausas et al, 2018; Bombo et al, 2022), critical traits for community productivity (Sarmiento, 1992) and carbon storage (Teixeira et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…When the environmental conditions become unfavorable during the dry season, both the above‐ and below‐ground components of the plant community are affected. At the above‐ground level, the aerial biomass dries up, increasing thus the amount of dead fuel load (Miranda et al, 2009; Rissi et al, 2017), and thus increasing the flammability of the system (Zanzarini et al, 2022). Since the dry seasons impose periods of water restriction, which dry the soil from the surface downward (Franco, 2002), at the below‐ground level, buds on below‐ground bud‐bearing organs may enter a dormancy stage (Ott et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Together with herbivory, fire and precipitation are major factors driving species distribution and the cyclicity between dry and wet seasons in savannas (Solbrig et al, 1996). By the end of the dry season, the herbaceous layer (mostly grasses) dries out, increasing the flammability of the system (Zanzarini et al, 2022). In general, fire is a natural disturbance that acts as a selection factor in fire‐prone ecosystems, and thus plants that invest in their persistence, such as the presence of a viable below‐ground bud bank that can rapidly resprout after the above‐ground removal of the biomass (Pausas et al, 2018), will be able to survive in these systems (Bond & Keeley, 2005; Simon & Pennington, 2012; Buisson et al, 2019).…”
Section: Introductionmentioning
confidence: 99%